Satisfying Information Needs on the Web: a Survey of Web Information Retrieval - Escudeiro,Nuno Filipe (2008)
Human kind felt, since early ages, the need to keep records of its achievements that could persist through time and that could be easily retrieved for later reference. Our own evolution depends largely on this iterative process, where each iteration is based on these records. The advent of the web and its attractiveness highly increased the availability of information which rapidly becomes ubiquituous. However, the lack of editorial control originates high heterogeneity in several ways. The traditional information retrieval techniques face new, challenging problems and prove to be inefficient to deal with web characteristics. In this paper we present a comprehensive and retrospective overview of web information retrieval.